Optimization of Time and Temperature Gelatin Extraction from Pink Perch (Nemipterus bathybius) Head using Response Surface Methodology (RSM) - Mardiyah, Ulfatul; Widjanarko, Simon Bambang; Fibrianto, Kiki (Graduate School, Universitas Brawijaya, 2019)
Gelatin from fisheries byproducts was very potential to be used as an alternative gelatin substitute for bovine and porcine gelatin. In this study, optimization of pink perch head gelatin extraction was carried out based on temperature and extraction time. Factorial design and Response Surface Methodology (RSM) were used to optimize the gelatin extraction process of pink perch (Nemipterus bathybius) head. The purpose of this research was to determine the optimum condition of the pink perch head extraction process based on the temperature and time of extraction. The extraction temperature (50°C - 90°C), and the extraction time (3 - 7 hours) were the independent variables. The response variables of this study were the yield of gelatin (%), gel strength (g.bloom) and viscosity (cP). The optimum extraction conditions were obtained at the extraction temperature of 74.40°C for 5.42 hours with a yield of 5.31%, the gel strength of 311.01 g.bloom and the viscosity of 5 cP. Considering its similarity to the commercial gelatin, particularly on their chemical characteristics, it can be suggested that the head of pink perch is a potential alternative of gelatin source. Keywords: Extraction, Gelatin, Optimization, Pink Perch Head